Psychological Scars Shouldn’t be Ignored: Addressing Factors Linked to Depression among Individuals with Laparoscopic Sleeve Gastrectomy - Abeer Selim; Emad Musaudi; Zohour Ibrahim Rashwan; Maha Alenezi; Rasha Alshalawi; Majd Nafea; Alya Shaib; Alyaa Ibrahim; Rasha Salah Eweida (SAGE Open Nursing)
Introduction Although bariatric surgeries have been linked to improved mental health, yet, some individuals develop depression. Objectives The present study aimed to assess the levels of depression and examine factors linked to depression among individuals with laparoscopic sleeve gastrectomy (LSG) in Saudi Arabia. Methods A cross-sectional design using a digital online survey was used to collect data. Depression was assessed using the Patient Health Questionnaire among individuals with LSG. Results A total of 344 eligible participants were included in the study. A significant percentage of the participants, almost one-third, were suffering from depression 27% ( n  = 94). Moderate to severe depression levels among participants were significantly associated with postoperative complications [odds ratio, OR: 2.92 (95% CI: 1.42–6.01, p  = .003)] and having preoperative psychological disorders before LSG [OR: 3.68 (95% CI: 1.88–7.26, p  < .001)]. In contrast, lower levels of depression were significantly associated with believing LSG has achieved its goals [OR: 0.46 (95% CI: 0.22–0.97, p  = .014)] and recommending LSG to family or friends [OR: 0.15 (95% CI: 0.05–0.44, p  = .001)]. Conclusion There is an evident link between depression and experiencing postoperative complications and suffering from psychological disorders before LSG. The findings of the current study would pave the road for the development of psychological strategies designed to break the cyclic pattern of occurrence of depression as well as optimize the success and maintenance of this treatment modality and support recovery for individuals undergoing LSG.